Prevalence and Hematological Profile of Gastrointestinal Bleeding Disorders in Rural Communities: A Clinicopathological Study - Rabbia Khalid Latif, Nomira Waheed, Fareena Almas, Abdul Wadood Shah, Muhammad Bilal, Abdul Karim Soomro (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Gastrointestinal (GI) bleeding is a common medical emergency associated with significant morbidity and mortality, particularly in rural populations where diagnostic and treatment resources are limited. This study aimed to assess the prevalence and hematological profiles of patients presenting with GI bleeding from rural communities in Pakistan. Methods: A cross-sectional study was conducted across multiple tertiary care hospitals from January 2022 to August 2023. A total of 110 adult patients from rural areas presenting with clinical signs of GI bleeding were enrolled. Detailed demographic, clinical, and hematological data were collected. Hematological parameters analyzed included hemoglobin, platelet count, prothrombin time (PT), activated partial thromboplastin time (aPTT), and international normalized ratio (INR). Data were analyzed using SPSS version 26. Results: Among the 110 patients, 64 (58.2%) were male and 46 (41.8%) were female, with a mean age of 48.3 ± 14.9 years. Upper GI bleeding was more prevalent (64.5%) than lower GI bleeding (35.5%). The majority of patients presented with moderate anemia (mean hemoglobin 10.15 ± 2.08 g/dL). Patients with upper GI bleeding had significantly lower hemoglobin and higher INR values than those with lower GI bleeding. Mild prolongation of PT and aPTT was also observed, especially in patients with suspected liver disease. Conclusion: GI bleeding in rural settings is predominantly upper GI in origin and frequently associated with anemia and borderline coagulopathies. Basic hematological testing remains a crucial tool for initial assessment in low-resource environments. Improved diagnostic capacity and early referral can significantly enhance outcomes in rural populations. Keywords: Gastrointestinal bleeding, anemia, rural health, hematology, coagulopathy, upper GI bleeding, Pakistan